An Organic–Inorganic Hybrid Exhibiting Electrical Conduction and Single‐Ion Magnetism. Issue 6 (21st January 2020) - Shen, Yongbing; Cosquer, Goulven; Ito, Hiroshi; Izuogu, David C.; Thom, Alex J. W.; Ina, Toshiaki; Uruga, Tomoya; Yoshida, Takefumi; Takaishi, Shinya; Breedlove, Brian K.; Li, Zhao‐Yang; Yamashita, Masahiro
Abstract: The first three‐dimensional (3D) conductive single‐ion magnet (SIM), (TTF)2 [Co(pdms)2 ] (TTF=tetrathiafulvalene and H2 pdms=1, 2‐bis(methanesulfonamido)benzene), was electrochemically synthesised and investigated structurally, physically, and theoretically. The similar oxidation potentials of neutral TTF and the molecular precursor [HNEt3 ]2 [M(pdms)2 ] (M=Co, Zn) allow for multiple charge transfers (CTs) between the SIM donor [M(pdms)2 ] n − and the TTF .+ acceptor, as well as an intradonor CT from the pdms ligand to Co ion upon electrocrystallisation. Usually TTF functions as a donor, whereas in our system TTF is both a donor and an accepter because of the similar oxidation potentials. Furthermore, the [M(pdms)2 ] n − donor and TTF .+ acceptor are not segregated but strongly interact with each other, contrary to reported layered donor–acceptor electrical conductors. The strong intermolecular and intramolecular interactions, combined with CT, allow for relatively high electrical conductivity even down to very low temperatures. Furthermore, SIM behaviour with slow magnetic relaxation and opening of hysteresis loops was observed. (TTF)2 [Co(pdms)2 ] (2‐Co ) is an excellent building block for preparing new conductive SIMs. Abstract : Magnetic personality : Electrocrystallisation of tetrathiafulvalene (TTF) and the magnetic precursor [Co(pdms)2 ] (H2 pdms=1, 2‐bis(methanesulfonamido)benzene) afforded a 3D conducting single‐ion magnet. Multiple charge‐transfer interactions between the components produce partial oxidation states for TTF, the Co ion, and the pdms ligand, allowing electrical conductivity at low temperatures.